How Does the New Keynesian Phillips Curve Forecast the Rate of Inflation in the Czech Economy? - Dřímal, Marek; Pošta, Vít, 1980-; Čadil, Jan; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
This analysis studies the phenomenon of the New Keynesian Phillips Curve - its inception from the RBC theory and DSGE modelling via incorporation of nominal rigidities, and its various specifications and empirical issues. The estimates on Czech macroeconomic data using the Generalised Method of Moments show that the hybrid New Keynesian Phillips Curve with the labour income share or the real unit labour cost as driving variables can be considered as an appropriate model describing inflation in the Czech Republic. Compared to other analyses, we show that the inflation process in the Czech Republic exhibits higher backwardness vis-a-vis other researchers' estimates based on US data.
Vedoucí práce: Vít Pošta
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses